THE EFFECT OF LEADERSHIP, WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Iin Indrayani; Mahfud (Journal Of Resource Management, Economics And Business, 2022)
Purpose: To determine and measure the influence of Leadership, Work Discipline, Work Motivation, either partially or jointly on Employee Performance at the Food and Agriculture Security Service. Research Methodology: This type of research is a causal associative research using a quantitative approach with the survey method. The population in this study were 206 agricultural extension workers from the Department of Food Security and Agriculture. The technique used in sampling in this study is by proportionate stratified random sampling using the Slovin formula as many as 68 people. Results: There is a partial influence of leadership on employee performance at the Department of Food and Agriculture Security by 87%. There is a partial effect of Work Discipline on the Performance of Food and Agriculture Security Service Employees of 89.6%. There is a partial influence of work motivation on the performance of employees of the Food and Agriculture Security Service of 82.7%. There is a positive and significant influence of leadership, work discipline and capacity simultaneously on the performance of employees of the Food and Agriculture Security Service. The magnitude of the positive influence of Leadership, Work Discipline, Work Motivation on Employee Performance is 95.1% while the remaining 4.9% is influenced by other factors. Limitations: Resecarh variable just Leadership, Work Discipline And Work Motivation On Employee Performance, need the development of other variables that support Contribution: Theoretically, the results of this study are expected to contribute ideas, especially in the science of human resource management as study material in the further development of theories of Leadership, Work Discipline and Work Motivation in an effort to improve employee performance.